Mediating Effects of Humor Styles on the Relationship Between Cognitive Flexibility and Interpersonal Problem-Solving Skills - Yerlikaya, Esef Ercüment; Karaçoban, Fatma (Anales de Psicología / Annals of Psychology, 2026)
The goal of this study was to test the mediating roles of humor styles in the relationship between cognitive flexibility and interpersonal problem-solving styles. A total of 425 students (324 females and 101 males) participated in the study. The results yielded that cognitive flexibility has significantly positive relationships with adaptive interpersonal problem-solving style, affiliative humor, and self-enhancing humor, whereas it has significant negative relationships with maladaptive interpersonal problem-solving style and aggressive humor. Adaptive humor styles were significantly positively correlated with adaptive interpersonal problem-solving styles and significantly negatively correlated with maladaptive interpersonal problem-solving styles. Maladaptive humor styles were significantly positively correlated with maladaptive interpersonal problem-solving style. The structural model tested in the study revealed that self-enhancing and aggressive humor styles play a partially mediating role in the relationship between cognitive flexibility and interpersonal problem-solving styles. These findings imply that interventions aimed at increasing students’ cognitive flexibility and self-enhancing humor style and decreasing aggressive humor style may enhance their adaptive interpersonal problem-solving styles.